Simplicity, inference and modeling : keeping it sophisticatedly simple - Zellner, Arnold; Keuzenkamp, Hugo A.; McAleer, Michael (Cambridge University Press, 2002)
The idea that simplicity matters in science is as old as science itself, with the much cited example of Ockham's Razor, 'entia non sunt multiplicanda praeter necessitatem': entities are not to be multiplied beyond necessity. Using a multidisciplinary perspective this monograph asks 'What is meant by simplicity?'